2011
DOI: 10.1248/cpb.59.799
|View full text |Cite
|
Sign up to set email alerts
|

A Simple, Iron-Catalyzed, Pyridine-Assisted Hydrogen Peroxide Epoxidation System

Abstract: A simple and inexpensive system comprised of H 2 O 2 -pyridine-FeCl 3 · 6H 2 O for the catalysis of olefin epoxidation was established. Intriguingly, the reactivity of this system greatly depends on the amounts of pyridine. Various substrates, including aromatic and aliphatic olefins, were epoxidized by this simple system in moderate to excellent yields.Key words hydrogen peroxide; iron(III) chloride; olefin epoxidation; pyridine; acceleration Epoxides are highly desirable building blocks for the formation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Another FeCl 3 catalyzed non-enantioselective epoxidation of alkenes with hydrogen peroxide was reported by Ishizuka and co-workers. 75 The authors propose an iron(III)-pyridine complex as in situ generated catalyst, which shows greater activity than for example the iron(III)-(N-methyl)imidazole complex. However, pyridine is applied in high excess (2 equiv.)…”
Section: Non-heme Iron-catalyzed Epoxidation Of Terminal Alkenesmentioning
confidence: 99%
“…Another FeCl 3 catalyzed non-enantioselective epoxidation of alkenes with hydrogen peroxide was reported by Ishizuka and co-workers. 75 The authors propose an iron(III)-pyridine complex as in situ generated catalyst, which shows greater activity than for example the iron(III)-(N-methyl)imidazole complex. However, pyridine is applied in high excess (2 equiv.)…”
Section: Non-heme Iron-catalyzed Epoxidation Of Terminal Alkenesmentioning
confidence: 99%
“…Even though the coordination structure of the most efficient catalyst was not provided, it was proposed that the peptide-based ligand bearing an N 2 O motif probably formed a biomimetic N 2 OFeCl 2 complex. Further catalytic approaches towards epoxide formation with non-heme iron complexes and H 2 O 2 or O 2 as environmentally friendly oxidants have been reported [19,20]. For example, in 2007 Beller and co-workers developed a remarkable method for the asymmetric epoxidation of aromatic alkenes using H 2 O 2 as oxidant [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Epoxidation of alkenes is an important transformation because epoxides are valuable synthetic intermediates . Development of catalytic epoxidation methods using an environmentally benign oxidant such as hydrogen peroxide is currently of interest because it produces water as the only waste byproduct and has advantages of cost and atom efficiency. , Methyltrioxorhenium (MTO, CH 3 ReO 3 ) is one of the most efficient and well-studied epoxidation catalyst using hydrogen peroxide as the oxidant. Since the original finding of the properties of MTO as an epoxidation catalyst in 1991, a large number of studies related to MTO-catalyzed epoxidation have been reported. , …”
mentioning
confidence: 99%